Implementasi Hak Nafkah ‘Iddah Istri Dalam Perkara Cerai Gugat berdasarkan PERMA No. 3 Tahun 2017 - Putri, Feby Lestari; Yusefri, Yusefri; Nasution, Aida Rahmi (Sakina: Journal of Family Studies, 2024)
The purpose of this study is to find out how the implementation of PERMA No. 3 of 2017 in divorce cases at the Curup Religious Court and to find out the considerations of the Curup Religious Court judges in the decision of case number 383/Pdt.G/2022/PA.Crp. This research is a field research with a type of Case study. The results of the study are as follows: First, the implementation of PERMA No. 3 of 2017 is applied by judges in every case related to women absolutely and is used as a reference during trials; The implication of PERMA for divorce cases is that the wife's 'iddah right can be fulfilled if the wife asks for her 'iddah right in the lawsuit and the fulfillment of the 'iddah right creates a sense of justice for the wife. Second, the judge's consideration in deciding case 383/Pdt.G/2022/PA. Crp is: the evidence presented by the plaintiff in his suit which is corroborated by witness statements and the absence of the defendant during the trial; consideration that case 383/Pdt.G/2022/PA. CRP occurred because the husband did something bad to the plaintiff, the defendant cheated, committed domestic violence and did not provide for 7 years; Based on the facts of the trial, the panel of judges held that the wife was not proven to be nusyuz so that the wife was entitled to her 'iddah rights in accordance with what was mandated in SEMA No. 3 of 2018.